Educational Games and Vocabulary Acquisition in Elementary School EFL Classes - Murad Tareq (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study explores elementary school teachers’ perspectives on the role of educational games in enhancing vocabulary acquisition among Arab students in Israel. Employing a qualitative approach, 15 teachers participated in semi-structured interviews to share their insights regarding the benefits, challenges, and strategies associated with game-based learning. The findings indicate that educational games significantly boost student engagement, foster motivation, and enhance vocabulary retention through interactive and culturally relevant experiences (Medina & Goddard, 2024). Teachers acknowledged several key challenges, including limited access to technology, the need to adapt games to meet diverse student needs, and the integration of assessments into the curriculum. They underscored the importance of professional development, culturally sensitive game content, and innovative strategies for implementation. This research highlights the potential of educational games to support language acquisition, bridge linguistic and cultural gaps, and improve learning outcomes for Arab students. These insights are intended to inform educational practices and contribute to the development of inclusive and effective learning environments.